Some New Characterizations Of Parallel Translation Surface According To Bishop Frame With Timelike M1 In Minkowski 3-Space - Suroglu, Gulden Altay (E D P Sciences, 2018)
In this paper We consider parallel translation surfaces, which arc generated by spacelike curves, according to Bishop frame with timelike M-1 in Minkowski 3-space. Then, we obtain some characterizations of these surface.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS